Effects of service supply chain practices on the profitability of tourism firms - Zailani, S.; Iranmanesh, M.; Yusof, N.; Ansari, R. (Taylor & Francis, 2015)
The tourism industry consists of various players and tourism demands that need to be addressed by a joint effort from all these players. The aim of this study is to investigate the effects of supply chain practices on the profitability of tourism firms. Data were gathered via a survey from tour operators. Results indicate that demand management, capacity and resource management, customer relationship management, supplier relationship management, order process management, service performance management, and information and technology management have an effect on the profitability of tourism firms. The findings of this study provide a useful tool for tourism firm managers to evaluate their current service supply chain (SSC) practices. Furthermore, the results confirm the IUE-SSC model in the tourism context.